Core questions and next steps in research on aggression in borderline personality disorder: rejoinder for "Aggression in borderline personality disorder - A multidimensional model" - Mancke, Falk; Herpertz, Sabine; Bertsch, Katja (Personality disorders, 2015)
Replies to comments by E. F. Coccaro (see record 2015-31349-002), J. D. Flory (see record 2015-31349-003), and L. N. Scott and P. A. Pilkonis (see record 2015-31349-004) on the original article (see record 2015-31349-001). With our response, we aim to address two of their core questions and suggest next steps for research on aggression in borderline personality disorder (BPD). (PsycINFO Database Record - (c) 2015 APA, all rights reserved).